If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(a+4)=3(a-2)
We move all terms to the left:
3(a+4)-(3(a-2))=0
We multiply parentheses
3a-(3(a-2))+12=0
We calculate terms in parentheses: -(3(a-2)), so:We get rid of parentheses
3(a-2)
We multiply parentheses
3a-6
Back to the equation:
-(3a-6)
3a-3a+6+12=0
We add all the numbers together, and all the variables
18!=0
There is no solution for this equation
| √2x+8=9 | | 31/5+x=7 | | ((5/y)-(5/(y-6))-6)=0 | | 7m/4=m-12 | | 4(2x-7)=49 | | -3(n+1)+7=-5 | | 2÷3(6x+30)=x+5(x+4)-2x | | 17=n-2 | | 6-3(2x+8)=39 | | 24=-6(m-3) | | 20÷x=4 | | 14-3m=-16 | | 3x2+7x=8 | | 6y-8=17y+25 | | 0.6=(2/x)+.4 | | C=85x+60C=85x+60 | | 0.6=2/x+.4 | | 4p+8p÷12=-48 | | 12-20x-35-28x+3=0 | | 6z-7=z+8 | | 4z/7+7=2 | | 6c-8+5-3c=14 | | 3-10=z/8 | | 4v+3.5=3v+3(-0.7+3v) | | 0=-7x+5x | | 2(b+1)=15 | | 5x+7x=95-7x | | (0,2);m=4/7 | | 5dd=8 | | 36=-2d+6 | | 3b+12/2=3 | | 77.1=55x-4.91x^2 |